Morphological Characterization of Four Leguminous Crops Cultivated in Two Agro Ecological Zone: Western and Guinean Savannah Highlands of Cameroon - Momo Wobeng Nelly Blondelle; Megueni Clautilde; Mandou Mouncharou Marie Solange; Madou Chantal; Mapongmetsem Pierre Marie (European Scientific Journal, ESJ, 2019)
In 2014, quarter (¼) of Africa populations were estimated to be suffering from hunger. In Cameroon, the demand for food is increasing while productivity was decreasing subsequently the food insufficiency. To solve this problem, leguminous crops were valorized in Cameroon. They represent a major source of protein especially among the poorest population, and are rich in essential amino acidssuch as lysine, supplementing thusthe nutritional value of cereal and tuber diets. Nevertheless, their production faced the problem of soil degradation and loss of soil fertility. The main objective of this work was to characterize leguminous crops cultivated in two agro ecological zones of Cameroon. Investigations based on farmer’s knowledge on leguminous crops cultivation were done in Western highlands and High Guinean savannah zones of Cameroon. During this survey, leguminous crops were collected for qualitative and quantitative analysis. Farmers which were mostly women have at least 10 years of experience on these leguminous crops cultivation. They kept their seed for next cultivation season and did not use fertilizers in their field. Based on color of seeds, nine, seven, six and four ecotypes of representing beans, peanuts, Bambara groundnuts and soybeans respectively were found from study sites. Quantitative analysis of these ecotypes presents the diversity of beans, peanuts and soybeans (p = 0.00) according to their biometric parameters. Except the weight of Bambara groundnuts which were different (p = 0.00) their size was similar among ecotypes.